What Is the Value of the Child and Dependent Care Credit? - Gabrielle Pepin (Institute of Labor Economics (IZA), 2024)
The Child and Dependent Care Credit (CDCC) subsidizes child care costs for working families. In response to the Covid-19 pandemic, the American Rescue Plan Act of 2021 increased the CDCC's generosity during 2021 only. I find that while the CDCC is of relatively little value in its current form, increases in eligibility rates and conditional benefits under the pandemic expansion increased the credit's value dramatically. Conditional on CDCC eligibility, higher-income households experienced the largest increases in benefit levels under the expanded CDCC, but lower-income households benefited disproportionately when measuring benefits as a share of income or child care spending.
Keywords: H24; J13; 330; Child and Dependent Care Credit; child care; American Rescue Plan Act of 2021; eligibility; benefits